Nonsense-mediated mRNA decay in genetic diseases and cancer: key players, mechanisms, and a novel approach for suppression therapy - Romão, Luísa (2019)
About one third of all genetic diseases and many forms of cancer are caused by nonsense or frameshift mutations that introduce premature translation-termination codons (PTCs) (1,2). Indeed, PTCs contribute significantly to the spectrum of inherited human diseases such as cystic fibrosis, Duchenne muscular dystrophy, beta-thalassemia, and many forms of cancer. Generally, the presence of a PTC results in premature termination of mRNA translation and in rapid degradation of the PTC-containing mRNAs through the mechanism of nonsense-mediated decay (NMD). Eukaryotic mRNA translation initiates with the recruitment of the cap-binding eukaryotic initiation factor 4F (eIF4F), which comprises eIF4E, eIF4A and eIF4G, to the mRNA 5’ end (3). eIF4G has a binding site for eIF4E and the cytoplasmic poly(A)-binding protein 1 (PABPC1), which in turn is bound to the poly(A) tail, resulting in mRNA circularization (4). The unwinding of the 5’UTR by the helicase eIF4A, enables binding of the 40S ribosomal subunit. The association of eIF1, eIF1A and eIF3 to the 40S subunit facilitates binding of the ternary complex eIF2-GTP-Met-tRNAi (3). The resulting 43S preinitiation complex can land next to the cap and scans in a 5’ to 3’ direction until it recognizes an AUG codon in a consensus sequence, base-pairing with Met-tRNAi (3). Then, there is joining of 60S subunit to form an 80S ribosome, and elongation can start and the polypeptide is synthesized (3). The termination event occurs when an elongating ribosome encounters an in-frame stop codon. The eukaryotic release factor 1 (eRF1) recognizes stop codons within the ribosomal A site and triggers the hydrolysis of the ester bond, stimulated by eRF3 (3). Interactions of the eRFs with cellular proteins playing key roles in other gene expression processes may be the means by which termination is adjusted and linked to mRNA translation and NMD. NMD controls the quality of eukaryotic gene expression and also degrades and controls the levels of physiologic mRNAs (1,2,5,6). The NMD pathway is found in all eukaryotes. Several NMD key factors are highly conserved among diverse species, including UPF1, UPF2, and UPF3 (1,2). Translating ribosomes normally displace the UPF2/UPF3 containing exon junction protein complexes (EJCs) from the open reading frame (ORF) during the pioneer round of translation (1,2). However, if an mRNA contains a PTC located more than 50-54 nucleotides upstream the last exon-exon junction, the ribosome will fail to displace distal EJC(s). If a PTC prohibits removal of distal EJCs from an mRNA during the initial round of translation, UPF1 and the SMG1 kinase associate with the eRF1 and eRF3 release factors on the ribosomal termination complex at the PTC. UPF1 then interacts with the UPF2/UPF3 proteins at the downstream EJC complex. This interaction induces UPF1 phosphorylation by SMG1 and marks the mRNA as PTC-containing (2). A complex composed of SMG5, SMG6, SMG7, and the PP2A phosphatase then dephosphorylates UPF1, and the mRNA is subsequently triggered to rapid decay by SMG6 endonucleolytic attack and exonucleolytic degradation from both 5’ and 3’ ends by a not yet completely understood process that recruits decapping and 5’-to-3’ exonuclease activities, as well as deadenylating and 3’-to-5’ exonuclease exosome activities (2,7). It has been shown that the catalytic subunits of the RNA exosome are the RNase II-family exoribonucleases DIS3 and DIS3L1 (8,9). Interestingly, DIS3L1 is mainly cytoplasmic, whereas DIS3 is mainly localized in the nucleoplasm (8,9). More recently, another RNase II homologue (DIS3L2) has been characterized (10), which is active in 3’-5’ cytoplasmic RNA decay, independently of the exosome (11). Despite the fact that DIS3L1 and DIS3L2 localize in the same compartment where NMD occurs, little is known about their role in this process. Nevertheless, it has been shown that mutations in the DIS3 locus are associated with aberrant accumulation of processing intermediates and aberrant forms of some RNAs (8), which evidences its essential role in RNA surveillance processes. In addition, significant findings over the last years have shown that human DIS3 paralogous are involved in growth, mitotic control, and important diseases such as cancer (8-10). For example, DIS3L2 inactivation was associated with mitotic abnormalities and altered expression of mitotic checkpoint proteins (10). Genetic diseases and cancer attributable to PTCs affect millions of patients worldwide. Thus, the high incidence of PTCs suggests that therapeutic strategies aimed at suppressing PTCs to restore deficient protein function – so-called suppression therapies – have the potential to provide a therapeutic benefit for many patients and with a broad range of genetic disorders (12,13). This therapeutic approach uses readthrough drugs, such as aminoglycosides, that induce the translational machinery to recode an in-frame PTC into a sense codon (12,13). Suppression therapy increases the frequency that near-cognate aminoacyl-tRNAs bind at a PTC and subsequently transfer their amino acid to the nascent polypeptide (12). However, there are several obstacles that must be overcome before aminoglycosides can be used long term in the suppression of nonsense mutations. First, the efficiency of suppressing PTCs is greatly influenced by the identity of the stop codon (TAA, TAG or TGA) and the surrounding mRNA sequence. Second, the long-term use of aminoglycosides is limited due to side effects (12,13). New strategies developed to overcome this issue include the discovery of non-aminoglycoside agents such as PTC124 (Ataluren®) (14), among others (12). While the most promising drug, PTC124, was found to be safe and offers a therapeutic benefit to many patients, not all patients respond equally well to its administration. One factor that possibly affects the response to suppression therapy in many patients is the high efficiency of NMD. Based on these data, this project included the following aims: (A) To study the role of DIS3-like proteins in the mRNA decay pathway inherent to NMD; (B) To analyze how DIS3L1 regulates the human transcriptome and how its functional interactions modulate the transcriptional reprogramming of colorectal cancer (CRC) cells; (C) To study the interplay between the mechanisms of PTC definition, mRNA translation, and NMD; (D) To establish an efficient PTC suppression therapy for beta-thalassemia.